Co-movements between Public and Private Wages in the EU: Which Factors Play a Role? - Benedicta Marzinotto; Alessandro Turrini (Institute for the Study of Labor (IZA), 2016)
This paper assesses the relationship between government and manufacturing wages. We find that the long-run relation between the two wages is stronger when the government is a large employer. Manufacturing wages are better aligned with productivity and unemployment when public wages, to which they respond, are set through bargaining. Finally, manufacturing wages react in the same way whether public wages are increased or cut, a relation that seems to hold also under fiscal consolidation provided the public sector is a large employer.
Keywords: C32; E24; E62; H59; 330; government wages; wage-setting; cost competitiveness; fiscal consolidation; cointegration